Structural health monitoring with non-linear sensor measurements robust to unknown non-stationary input forcing. (1st May 2021) - Sen, Subhamoy; Aswal, Neha; Zhang, Qinghua; Mevel, Laurent
Highlights: Interacting Particle and Ensemble filter is used to track structural damages online. Ensemble filter extends the reach of interacting strategy to nonlinear systems. Robustness against nonstationary excitation is achieved by output injection strategy. The data are combining measurements from accelerometers and strains. The algorithm is tested on numerical frame structures excited by El Centro benchmark. Abstract: Bayesian filtering based structural health monitoring algorithms typically assume stationary white Gaussian noise models to represent an unknown input forcing. However, typical structural damages occur mostly under the action of extreme loading conditions, like earthquake or high wind/waves, which are characteristically non-stationary and non-Gaussian. Clearly, this invalidates this basic assumption, causing these algorithms to perform poorly under non-stationary noise conditions. This paper extends an existing interacting filtering algorithm to efficiently estimate structural damages while being robust to unknown non-stationary non-Gaussian input forcing. Furthermore, this approach is generalized beyond linear measurements to encompass the case of non-linear measurements such as strains. The joint estimation of state and parameters is performed by combining Ensemble Kalman filtering, for non-linear system state estimation, and Particle filtering to estimate changes in the structural parameters. The robustness against input forcing is achieved through an output injection approach embedded in the state filter equation. Numerical simulations for two kinds of response measurements (acceleration and strain) are performed on a 3D frame structure under different damage location and severity scenarios. The sensitivity with respect to noise and the impact of different sensor combinations have also been investigated.